The Effect of Family Harmony and Peers Social Interaction on Emotional Maturity - Suwendra, I Wayan (Opción, 2019)
The aim of the study is to investigate the effect of family harmony and peers social interaction on emotional maturity via quantitative, descriptive and correlation research methods. As a result of research from SEM Amos 4.01 analysis, there were significant direct effects of family harmony toward emotion maturity toward students’ attitude. In conclusion, there is a direct and indirect relationship between the harmony of the family, peer social interaction, emotional maturity, attitude and self-concept in relation to the practice of teaching Tri Kaya Parisudha.